Improvement of dissolution rate of poorly water-soluble drug by wet grinding with bio-compatible phospholipid polymer. (24th March 2015) - Watano, Satoru; Matsuo, Mika; Nakamura, Hideya; Miyazaki, Tsuyoshi
Abstract: An innovative technology to enhance drug dissolution rate was proposed in this study. Poorly water-soluble ibuprofen was ground in a bio-compatible and amphiphilic co-polymer solution made from 2-methacryloyloxyethyl phosphorylcholine (MPC) and butylmethacrylate (BMA) by using a novel multi-ring type wet grinding system. The dry particle of ibuprofen was produced by freeze drying of the slurry obtained by the wet grinding. It was found that the dissolution rate of ibuprofen was enhanced incredibly. Effect of the polymer content on the dissolution rate, size of ibuprofen particle in slurry and the crystallinity change was investigated. The effect of size decrease (increase in apparent interfacial contact area) and the crystallinity decrease contributed to enhance the dissolution rate. However, the most significant factor that dramatically enhanced the dissolution rate was the effect of bio-compatible and amphiphilic MPC polymer. Owing to the hydrophobic interaction, the hydrophobic surface of ibuprofen was covered by the hydrophobic polymer chain of the MPC polymer, facing its hydrophilic groups to water when the dry ibuprofen particle was dissolved in water. The "surfactant effect" contributed very much to enhance the initial dissolution rate of ibuprofen significantly. Graphical abstract: Highlights: An innovative technology to enhance drug dissolution rate was proposed. Wet grinding of ibuprofen was conducted in a bio-compatible and amphiphilic co-polymer solution. A novel multi-ring type wet grinding system was used. Hydrophobic interaction between polymer and drug contributed very much to, enhance the dissolution rate. Dissolution rate of ibuprofen at 1 min was enhanced 69 times as fast as the, original one.